ARTIFICIAL INTELLIGENCE IN DETECTING ATHEROSCLEROSIS PLAQUES AND ELECTROMAGNETIC THERAPY TO ALTER CHOLESTEROL LEVEL - Florentina D Pramesuari (JOURNAL OF WIDYA MEDIKA JUNIOR, 2022)
Introduction: Artificial Intelligence (AI) application in healthcare fields include matching patient symptoms to appropriate physician, helped to diagnose patients, determine patient’s prognosis, drug discovery, translating languages, and organize data. AI technology used in analysis and diagnosing coronary atherosclerotic plaques has increased annually. There are studies suggested that extremely low-frequency electromagnetic fields exposure can affect lipid metabolism.Purpose: To use applied AI in a device that can both identifying atherosclerosis in blood vessel and treat with low-frequency electromagnetic wave.Method: Experiments carried out using a device to detect and treat blockage of blood vessels by emitting electromagnetic signals. This tool is an AI breakthrough that not only includes a diagnostic function, but can also perform electromagnetic therapy.Result: Previous studies mentioned that AI can be applied to identify atherosclerosis. There are some studies that states low-frequency electromagnetic waves can alter HDL and cholesterol levels in blood. Larger studies are needed to combine both function in identify atherosclerosis plaques and electromagnetic therapy.Conclusion: Rapidly developing AI technology can be applied to identify atherosclerosis plaque and treat them. Further studies are required to provide definitive proof of electromagnetic wave effects on the removal of cholesterol from plaques using thermal effects or raising HDL concentrations in blood.